Produção de sideróforos e hormônio de crescimento vegetal do tipo ácido indolacético por bactérias diazotróficas provenientes de nódulos de mimosa spp. em solos ultramáficos - Bortolotti, Vera Lúcia (2014)
Metals excess and the low availability of nutrients are characteristic of ultramafic soils. It’s results in strong mineral imbalance and stimulates the occurrence of plant species adapted to these conditions. The presence of this flora is related to a close association with the rhizosphere microorganisms which contributes to its adaptability. An important group of endogenous microbiota consists of diazotrophs. Plants from the genus Mimosa are listed among the predominant species in ultramafic soils from Barro Alto (GO). Besides the biological nitrogen fixation, bacteria symbiotically associated with these plants can promote plant growth through the production of phytohormones such as indole acetic acid (IAA). Additionally, these bacteria may excrete siderophores, organic molecules capable of sequestering Fe, among other metals, which may alter the availability of toxic elements in the rhizosphere. In this context, this proposal aims to evaluate the production of IAA and siderophores by diazotrophic bacteria isolated from nodules of Mimosa spp. found in the ultramafic massif of Barro Alto (GO). Among the evaluated isolates, three (W5, W15 and W24) stood out because they were able to produce siderophores and greater amounts of AIA. These isolates would be interesting candidates for evaluation tests of plant growth promotion aiming their use in recovery programs for areas degraded by mining activity.